2008
DOI: 10.1186/1742-4690-5-100
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-146a and further oncogenesis-related cellular microRNAs are dysregulated in HTLV-1-transformed T lymphocytes

Abstract: Background: Human T-lymphotropic virus type 1 (HTLV-1) is the etiologic agent of a severe and fatal lymphoproliferative disease of mainly CD4 + T cell origin, adult T cell leukemia, which develops after prolonged viral persistence. Transformation of infected cells involves HTLV-1's oncoprotein Tax, which perturbs cell cycle regulation and modulates cellular gene expression. The latter function is also a hallmark of microRNAs, a rather new layer in the regulation of gene expression. Affecting e.g. proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
124
2
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(138 citation statements)
references
References 73 publications
7
124
2
5
Order By: Relevance
“…An emerging body of evidence suggests that miRNAs are often overexpressed or downregulated in a number of human malignancies, and these genes are thought to function as tumor suppressors or oncogenes (Ambros, 2004). Recent studies demonstrate that various viruses, including human T-cell leukemia virus type 1 and Epstein-Barr virus, disturb the physiological functions of host cells by altering cellular miRNAs expression, leading to changes in cell proliferation or to a malignant phenotype (Connolly et al, 2008;Godshalk et al, 2008;Pichler et al, 2008;Tomita et al, 2009). Based on these observations, we speculate that particular genes targeted by miRNA might be involved in the process of SV40 ST-induced cell transformation.…”
Section: Introductionmentioning
confidence: 77%
“…An emerging body of evidence suggests that miRNAs are often overexpressed or downregulated in a number of human malignancies, and these genes are thought to function as tumor suppressors or oncogenes (Ambros, 2004). Recent studies demonstrate that various viruses, including human T-cell leukemia virus type 1 and Epstein-Barr virus, disturb the physiological functions of host cells by altering cellular miRNAs expression, leading to changes in cell proliferation or to a malignant phenotype (Connolly et al, 2008;Godshalk et al, 2008;Pichler et al, 2008;Tomita et al, 2009). Based on these observations, we speculate that particular genes targeted by miRNA might be involved in the process of SV40 ST-induced cell transformation.…”
Section: Introductionmentioning
confidence: 77%
“…For example, in the study by Yeung et al, the authors reported that the tumor suppressor protein TP53INP1 in HTLV-1-infected/transformed cells was targeted for repression by the upregulated expression of miR-93 and miR-130b [27]. By comparison, in the subsequent study by Pichler et al, TP53INP1 was also reported to be targeted in HTLV-1 infected/transformed cells, but by the upregulated expression of miR-21, -24, -146a, and -155 [28]. Remarkably, separate from the in vitro HTLV-1 infected/transformed cells, Bellon et al and Yeung et al further investigated in vivo ATL leukemic cells from patients; and both noted upregulated miR-155 expression [27,29] which would be consistent with a silencing of TP53INP1 by miR-155 [31].…”
mentioning
confidence: 90%
“…Later, miRNA signatures for various cancers were described and linked to oncogenic transformation and found to be diagnostic of tumor types [23,26]. The deregulated expression of miRNAs in HTLV-1 transformed cells has also been reported in three independent publications [27][28][29]. In parsing the specific miRNA changes published in the three HTLV-1 studies, there appears to be very little over lap amongst most of the miRNA moieties [30].…”
mentioning
confidence: 97%
“…Recent studies have shown the interactions between HTLV-1 and the miRNA regulatory network. miRNA expression profiling studies in HTLV-1-infected T-cell lines and ATLL patients samples have been performed by some groups (Pichler et al, 2008;Yeung et al, 2008;Bellon et al, 2009) (miR-9, miR-17-3p, miR-20b, miR-93, miR-130b, and miR-18a) are upregulated and 9 mi-RNAs (miR-1, miR-144, miR-126, miR130a, miR-199a*, miR-338, miR-432, miR-335, and miR-337) are downregulated both in HTLV-1-transformed cell lines and primary ATLL cells (Yeung et al, 2008). To distinguish miRNAs that are responding to proliferative stimuli, they also examined PBMC exposed to phorbol-12-myristate 13-acetate (PMA) compared to untreated PBMC.…”
Section: Adult T-cell Leukemia/lymphoma (Atll)mentioning
confidence: 99%